PENGARUH GAYA KEPEMIMPINAN TRANSACTIONAL, TRANSFORMATIONAL, AUTHENTIC DAN AUTHORITARIAN TERHADAP KINERJA GURU MADRASAH TSANAWIYAH DI KUDUS - Agus Purwanto; Ardian Sopa; Riza Primahendra; Sekundina Williana Kusumaningsih; Rudy Pramono (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2020)
This study aims to analyze the effect of transactional, transformational, authentic and authoritarian leadership styles on the performance of Madrasah Tsanawiyah teachers in Kudus, Central Java. Teacher performance can be improved when there is a match between work and their expertise, as well as teacher placement in their assignments. This study uses a quantitative approach with survey. The data collection technique was carried out through the distribution of online electronic questionnaires to Madrasah Tsanawiyah teachers in Kudus, Central Java. Data analysis in this study uses SEM (Structural Equation Model) LISREL program version 8.70. The results of the analysis and processing of research data indicate that; Transactional and authoritarian leadership styles in Madrasah Tsanawiyah in Kudus have a positive and significant effect on improving teacher performance. While the transformational and authentic leadership style does not significantly influence the performance of teachers in the Madrasah Tsanawiyah in Kudus, Central Java.